Evaluation of the antibacterial effects of Eucalyptus camaldulensis L., Glycyrrhiza glabra L. and Morus nigra L. extracts against some pathogenic bacteria in vitro - Sidkey, Ban A. J.; Omran, Afrah H. (Iraqi Journal of Science, 2021)
This study aimed to test the effect of using different concentrations of three different plants extracts to inhibit the growth of gram negative and gram positive bacteria by two technics. Eucalyptus camaldulensis bark, Glycyrrhiza glabra rhizomes and Morus nigra leaves ethanolic extract at (0,20,30,40 and 50 mg/ml) were used. The antimicrobial activity and the biofilm inhibition assay used with these extracts showed positive effect in inhibiting the growth of bacteria. E.amaldulensis extract showed the higher effect than G. glabra and M.nigra extracts in antimicrobial activity assay, while the effect of E. camaldulensis extract in biofilm inhibition assay was higher than G. glabra that was higher than M. nigra extracts for both gram negative and positive bacteria. These results confirmed the effect of E. camaldulensis, G. glabra and M. nigra extracts on retarding the growth of bacteria.